The role of user experiences towards responsive web / Saidatul Amalina Md Salleh Huddin and Muhamad Fairus Kamaruzaman - Md Salleh Huddin, Saidatul Amalina; Kamaruzaman, Muhamad Fairus (Universiti Teknologi MARA, 2018)
In today's growing world of technology, User Experiences (UX) known as a vital to the end user especially in the field of Human-Computer Interaction (HCI). The initial requirement for an exemplary UX is to meet the specific needs of customer without hassle. It also noted that, the UX role towards responsive web design is also connected to the Joomla open sources system. Joomla is a great Content Management System (CMS) with a lot of flexibility. However, to establish the website, empathizing UX is the key fundamental architecture in order to create the website skeleton before crafting the tangible HCI. Most public university website in Malaysia are using Joomla as their medium to interact with the world and this include Faculty of Art & Design, Universiti Teknologi MARA (UiTM) Shah Alam, Selangor. This research paper will present the scholars perspective on UX and will examine its implications in the HCI domain.